Combined transgenic expression of α-galactosidase and α1,2-fucosyltransferase leads to optimal reduction in the major xenoepitope Galα(1,3)Gal - Osman, Narin (The National Academy of Sciences of the USA, 1997)
Hyperacute rejection of pig organs by humans involves the interaction of Galα(1,3)Gal with antibodies and complement. Strategies to reduce the amount of xenoantigen Galα(1,3)Gal were investigated by overexpression of human lysosomal α-galactosidase in cultured porcine cells and transgenic mice. The overexpression of human α-galactosidase in cultured porcine endothelial cells and COS cells resulted in a 30-fold reduction of cell surface Galα(1,3)Gal and a 10-fold reduction in cell reactivity with natural human antibodies. Splenocytes from transgenic mice overexpressing human α-galactosidase showed only a 15–25% reduction in binding to natural human anti-Galα(1,3)Gal antibodies; however, this decrease was functionally significant as demonstrated by reduced susceptibility to human antibody-mediated lysis. However, because there is residual Galα(1,3)Gal and degalactosylation results in the exposure of N-acetyllactosamine residues and potential new xenoepitopes, using α-galactosidase alone is unlikely to overcome hyperacute rejection. We previously reported that mice overexpressing human α1,2-fucosyltransferase as a transgene had ≈90% reduced Galα(1,3)Gal levels due to masking of the xenoantigen by fucosylation; we evaluated the effect of overexpressing α-galactosidase and α1,2-fucosyltransferase on Galα(1,3)Gal levels. Galα(1,3)Gal-positive COS cells expressing α1,3-galactosyltransferase, α1,2-fucosyltransferase, and α-galactosidase showed negligible cell surface staining and were not susceptible to lysis by human serum containing antibody and complement. Thus, α1,2-fucosyltransferase and α-galactosidase effectively reduced the expression of Galα(1,3)Gal on the cell surface and could be used to produce transgenic pigs with negligible levels of cell surface Galα(1,3)Gal, thereby having no reactivity with human serum and improving graft survival.